Sistem Informasi Pelayanan Donor Darah Berbasis Web Pada Palang Merah Indonesia (PMI) Kota Jambi - Saputri, Saemona Maharani; Sarjono, Sarjono (LPPM Universitas Dinamika Bangsa, 2021)
In blood donor services, the Indonesian Red Cross (PMI) of Jambi City found problems like information regarding the blood stocks and blood donors availability is difficult to obtain, blood donor services dissemination is slow and high doubt of patients about the quality of blood. The research objective is to analyze and design the information system for blood donor services using the PHP language programming and MySQL database. Furthermore, the research methodology used the waterfall model and the unified model language system using use-case diagrams, activity diagrams, and class diagrams. The conclusion of the system can display the donor data, blood donor data, information data, forum data in structured and display the required reports. The research suggests that the prototype of this system needs to develop well and correctly so that it can be applied to the Indonesian Red Cross (PMI) of Jambi City